2022
DOI: 10.1155/2022/3109212
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Thermodynamic Studies on the Biosorption of Lead (II) by Living and Nonliving Biomass of Penicillium notatum

Abstract: This study aims to investigate the biosorption of Pb (II) by living and nonliving biomass of Penicillium notatum. Penicillium notatum PTCC 5074 was purchased from Iran Scientific-Industrial Research Organization in lyophilized form and after culturing in potato dextrose agar was propagated in Sabouraud dextrose broth medium. The highest adsorption by living and nonliving biomass (180.74 and 187.08 mg/g per dry weight of biomass, respectively) was at the Pb (II) concentration of 228 mg/L and ionic strength of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Here, q e (mg.g − 1 ) is the equilibrium adsorption capacity. C e (mg.L − 1 ) is the equilibrium concentration of the adsorbent, and K and n are the Freundlich constants obtained in the curve logqe vs. logCe [47,48]. Te results showed that the adsorption in TWMNPs follows the Langmuir model (R 2 = 0.963), and the maximum adsorption capacity of Pb (II) on to the TWMNPs at 10.67 mg.g − 1 indicated the ability of the TWMNPs for adsorption of Pb (II).…”
Section: Adsorption Isothermmentioning
confidence: 96%
See 2 more Smart Citations
“…Here, q e (mg.g − 1 ) is the equilibrium adsorption capacity. C e (mg.L − 1 ) is the equilibrium concentration of the adsorbent, and K and n are the Freundlich constants obtained in the curve logqe vs. logCe [47,48]. Te results showed that the adsorption in TWMNPs follows the Langmuir model (R 2 = 0.963), and the maximum adsorption capacity of Pb (II) on to the TWMNPs at 10.67 mg.g − 1 indicated the ability of the TWMNPs for adsorption of Pb (II).…”
Section: Adsorption Isothermmentioning
confidence: 96%
“…In order to determine the absorption capacity of an adsorbent, this parameter is an important and efective factor. In order to determine the adsorption mechanism, Langmuir and Freundlich isotherms were used in this research [47,48]. Te linear equation of the Langmuir isotherm is given in equations ( 9) and (10).…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that produced iron oxide is in the form of Fe 3 O 4 . Te achieved mixture was dried in an oven at 100 °C for 2 hours [22,[25][26][27].…”
Section: Synthesis Of Mwcnts-fe 3 Omentioning
confidence: 99%
“…Tis parameter is a key factor in determining the capacity of an adsorbent and optimizing the adsorbent consumption. In this study, Langmuir and Freundlich adsorption isotherms were used to investigate the adsorption mechanism [22,26,27,42]. Linear equation of the Langmuir isotherm is given in the following equation:…”
Section: Adsorption Isothermsmentioning
confidence: 99%